Kontribusi perikanan pukat cincin yang berpangkalan di Pelabuhan Perikanan Pantai Tumumpa terhadap PDRB Kota Manado di masa Covid-19 - Elvan Sembiring; Effendi P. Sitanggang; Ixchel F. Mandagi (Universitas Sam Ratulangi, 2024)
Covid-19 brought their intensive effects in marine fishery subsector in Manado by the end of 2019. The research aimed at finding out how far the effect of purse seine fishery contribute on Gross Regional Domestic Product (GRDP) Manado between before and after Covid-19. Secondary data collected from of BPS Manado dan North Sulawesi in 2018 - 2022, while primary data i.e purse seiner’s catches and its value production from the annual reports of Tumumpa coastal fishing port by direct observation on board. Data was analyzed using Location Quotient (LQ) approach. The result of data analysis showed, there was a declining production during Covid-19 due to a lack of fishing operation activities, having a consequence in fish production value decreasing, because the fish distribution obstruction from the centres of producer to the centres of consumer. Before Covid-19 period, it gained the average catches of 10,7 million tons.yrs-1 (increasing 17,46% yrs-1), with production value of Rp. 159,6 billion yrs-1 (increase 23,23% yrs-1). During Covid-19, average cathes of purse seiner was 11,3 billion tons yrs-1 (decline 8,25% yrs-1) and production value of Rp. 204,3 billion yrs-1 in average (decline of 8,30% yrs-1). Purse seine fishery contribution on GRDP Manado decrease from 0,10% yrs-1 before Covid-19 (2017-2019) to - 0.42% yrs-1 during Covid-19 (2020-2012). During these two periods, (marine) fishery subsector had a LQ < 1, meant that this subsector was really not a basis of the subsector. To fulfill the Manado society consumption on fishes, it is required to supply fishes from other locations. The other side, the business of purse seiner fishery brought an agreeable advantage.